Simply tuning the electron deficient units to achieve P and N-type conjugated polymers for organic solar cells. (March 2019) - Yang, Lei; Ye, Pan; Gu, Wenxing; Lv, Lei; Chen, Yusheng; Dong, Tao; Guan, Qian; Peng, Aidong; Huang, Hui
Abstract: D-A strategy and noncovalent conformational locks (NCLs) have been employed as important tools to construct highly performing conjugated polymers (CPs). In this work, a donor (D) unit (E)- 1, 2-diethoxy-1, 2-bis(5-(trimethylstannyl)thieno[3, 2-b]thiophen-2-yl)ethene (FS) with S⋯O NCLs was copolymerized with four different acceptor (A) units. Upon changing the electron deficient properties of the A unit, the electronic properties of the CPs were successfully tuned to afford two p-type CPs and two n-type CPs. The optical absorption, electrochemical properties, molecular geometries, photovoltaic properties, charge transport characteristics, and morphology of these polymers and corresponding devices were systematically investigated. P-type polymer PffBT2T-FS and n-type polymer PPDI-FS based devices achieved PCEs as high as 5.03% and 3.23%, respectively. This contribution provides a synthetic strategy for constructing novel high-performance CPs. Highlights: A donor unit FS with S⋯O noncovalent conformational lock was employed to yield four polymers. P- and N-type Conjugated Polymers were obtained by simply tuning the electron deficient units. This contribution provides a synthetic strategy for constructing novel high-performance polymers.